Al-Jahalah wa al-Jahiliyyah fi al-Qur’an (Dirasah Tahliliyyah fi al-Dalalah al-Qur’aniyyah) - Sujiat Zubaidi Saleh (Cordova Journal : languages and culture studies, 2022)
Without a doubt, we know that in the Al Quran there are miracles in terms of balanghai, sharia, meaning, lafadh and uslub. One of the interesting things in the Al Quran is the words jahalah and jahiliyyah. So this study intends to reveal the meaning of the words jahalah and jahiliyyah etymologically and also to reveal the meaning of the terminology of both when related to the context in the Al Quran. The research used the semantic method with data sourced from the Al Quran and then analyzed by reading the interpretations of the Tafsir Al Quran. From this research it can be found that although these two words have the same origin, they have different meanings. Then it was also found that the word jahalah is not always for insult, so there are 4 levels jahalah. Meanwhile, jahiliyyah although this characteristic is often associated with the era before the prophet, but can also occur after the time of the prophet, by looking at the signs of ignorance in the Al Quran